Pengaruh Product, Price, Place, dan Promotion Terhadap Keputusan Pembelian - Andika Prabowo; Suwarto; Selamet Fuadi (Universitas Muhammadiyah Metro, 2026)
Based on field findings, it was found that the number of purchases at Warung Abnormal Metro City fluctuated every month. This purchasing decision is influenced by various factors that influence it. So the aim of this research is to determine the influence of product, price, place, promotion on purchasing decisions at Warung Abnormal Metro City. This research is quantitative research. With this type of explanatory survey research, the sampling technique was accidental sampling, as many as 70 visitors were met during the research. As a measuring tool, a 100-item questionnaire was used with Likert scale measurements and analyzed using multiple regression analysis. The research results show that the product has a positive and significant influence on purchasing decisions at Warung Abnormal, Metro City. Price has a positive and significant effect on purchasing decisions at Warung Abnormal Kota Metro. Place has a positive and significant effect on purchasing decisions at Warung Abnormal Kota Metro. Promotion has a positive and significant effect on purchasing decisions at Warung Abnormal Kota Metro. product, price, place, promotion together have a positive and significant influence on purchasing decisions at Warung Abnormal Metro City.